Halogen sensing using thin films of crosswise-substituted phthalocyanines - (:unkn) unknown (ELSEVIER SCIENCE SA, 2001)
Organic compound phthalocyanines (Pcs) are able to act as chemically sensitive films because of the various physical effects induced in them by interaction with a large number of gases. Specifically, they are used as thin film semiconducting gas sensors for the detection of halogens such as chlorine (Cl-2) and nitrogendioxide (NO2) as well as organic vapors. In a systematic test of different materials, crosswise-substituted with two alkylsulfanyl and two amino groups phthalocyanine films were investigated as sensitive materials for the detection of halogens. The sensing properties of these films were investigated by measuring both de and ac conductivity changes as a function of the gas concentration (0.05-0.15 ppm) at different temperatures (5-75 degreesC). The electrical properties of the films were determined by means of de and ac conductivity measurements under vacuum and without vacuum. The results show that the conductivity curve goes through a maximum at a certain temperature, T-max, depending on the molecular structure of the phthalocyanine films. The gas sensing measurements show that the sensors are highly sensitive to very low concentration of Br-2 and Cl-2 gases. The sensor signals are nearly reversible and reproducible even at room temperature. The crosswise substituted phthalocyanine thin films have good selectivity. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: halogen; phthalocyanines; conductivity; LANGMUIR-BLODGETT-FILMS; ELECTRICAL-PROPERTIES; COPPER PHTHALOCYANINE; LEAD PHTHALOCYANINE; CONDUCTIVITY; DERIVATIVES; SENSORS